Design of an obstacle and collision avoidance system for multi-mobile robot coordination - Huang, Kelvin Jin Chong (Nanyang Technological University, 2020)
Multi-robot coordination has a wide range of useful applications in autonomous vehicles, logistics planning, cooperative inspection and many more. While these robots are moving and attempting to achieve their targeted goals, these robots will have to deal with static and dynamic obstacles. Static obstacles are stationary objects or people that would obstruct the robots’ path of motion. Dynamic obstacles are the moving objects or people that would obstruct the robots’ path of motion and the movement of the rest of the robots have to be considered in obstacle and collision avoidance. The purpose of this project is to design an obstacle and collision avoidance module for a multi-robot system containing of multiple mobile robots. The scope of the project covers the development of an obstacle and collision avoidance solution for multiple robots as well as testing the results using multiple robots through simulations. This paper aims to study the existing methods used for obstacle avoidance for a single robot and applying them to multi-mobile robot coordination with simulations using MATLAB.